Management of Unsignalized Intersections (Case Study of Duren Intersection, Ciputat District) - Muhammad Farid Renandes; A.R Indra Tjahjani; Pio Ranap Tua Naibaho (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2025)
Traffic congestion leads to significant losses in the form of extended travel times, fuel waste, and environmental degradation. This congestion primarily results from traffic volumes exceeding both highway and intersection capacities. To address these issues and ensure smooth traffic flow, it is crucial to evaluate intersection performance. This study focuses on the Duren Intersection in South Tangerang City, where Merpati Raya Street, Menjangan Raya Street, Cenderawasih Street, and KH. Dewantoro Street converge. The current situation at the Duren Intersection continues to cause congestion, as evidenced by traffic performance data. On weekdays during peak hours, the average vehicle queue length reaches 192.03 meters, with an average traffic delay of 42.153 seconds per vehicle, resulting in a Level of Service (LOS) E. On holidays, the peak hour average queue length is 128.71 meters, with an average delay of 25.126 seconds per vehicle, corresponding to a LOS D. Given these conditions, this study, titled